The Almanack Of Naval Ravikant: A Guide to Wealth and Happiness - Jorgenson, Eric; Butcher, Jack (Gurugram: HarperCollians, 2020)
Getting rich is not just about luck; Happiness is not just a trait we are born with. These aspirations may seem out of reach, but building wealth and being happy are skills we can learn. So what are these skills, and how do we learn them? What are the principles that should guide our efforts? What does progress really look like? Naval Ravikant is an entrepreneur, philosopher, and investor who has captivated the world with his principles for building wealth and creating long-term happiness. The Almanack of Naval Ravikant is a collection of Naval$1 (Bs wisdom and experience from the last ten years, shared as a curation of his most insightful interviews and poignant reflections. This isn$1 (Bt a how-to book, or a step-by-step gimmick. Instead, through Naval$1 (Bs own words, you will learn how to walk your own unique path toward a happier, wealthier life.s
Includes appreciation, sources and other book recommendations
Keywords: Wealth$1 (BPsychological aspectss -- Happiness$1 (BPhilosophys -- Self-actualization; Success in business$1 (BPhilosophys -- Conduct of life -- Entrepreneurs$1 (BUnited States$1 (BBiographys